2011
DOI: 10.1523/jneurosci.1250-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Role of the CaMKII/NMDA Receptor Complex in the Maintenance of Synaptic Strength

Abstract: During long-term potentiation (LTP), synapses undergo stable changes in synaptic strength. The molecular memory processes that maintain strength have not been identified. One hypothesis is that the complex formed by the Ca2+/Calmodulin -dependent protein kinase II (CaMKII) and the NMDA-type glutamate receptor (NMDAR) is a molecular memory at the synapse. To establish a molecule as a molecular memory, it must be shown that interfering with the molecule produces a persistent reversal of LTP. We used the CN class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
258
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(267 citation statements)
references
References 59 publications
8
258
0
1
Order By: Relevance
“…In future, it will be interesting to test whether the interaction between the NMDA receptor subunit GluN2B and aCaMKII contribute to memory storage, as this interaction appears to be required for LTP maintenance (Sanhueza et al 2011). In agreement with this idea, point mutations in GluN2B that impair GluN2B/ CaMKII interaction cause a deficit in spatial memory retention, although LTP was not fully blocked and spatial learning was unaffected (Halt et al 2012).…”
Section: Camkiimentioning
confidence: 89%
“…In future, it will be interesting to test whether the interaction between the NMDA receptor subunit GluN2B and aCaMKII contribute to memory storage, as this interaction appears to be required for LTP maintenance (Sanhueza et al 2011). In agreement with this idea, point mutations in GluN2B that impair GluN2B/ CaMKII interaction cause a deficit in spatial memory retention, although LTP was not fully blocked and spatial learning was unaffected (Halt et al 2012).…”
Section: Camkiimentioning
confidence: 89%
“…In fact, T286 phosphorylation induced by LTP stimuli may only be very short lived (63). However, a recent study indicated that storage of synaptic memory previously proposed to be mediated by T286 phosphorylation can instead be mediated by the NMDA receptor-bound form of CaMKII (30), and it will be interesting to examine the functional contribution to memory in behavioral studies.…”
Section: Discussionmentioning
confidence: 99%
“…22 CaMKII and the NMDA receptor that were found in postischemic insoluble aggregates (Table 1) form a complex that has a role in long-term potentiation. 26 Long-term potentiation is one of the major mechanisms underlying learning and memory. 27 Activity levels of neurons control the postsynaptic composition and signaling by modulating the composition of the postsynaptic density by reversible activation of ubiquitin conjugation/ deconjugation.…”
Section: Proteomics Of Postischemic Ubiquitin Aggregates M Iwabuchi Ementioning
confidence: 99%